Bidding strategy optimization for power generation company in carbon emission rights and electricity market. (August 2022) - Wang, Pei; Tang, Jiajun; Zhang, Zhi; Li, Yating; Wu, Hao; Ji, Chao; Lin, Zhemin; Ma, Jien; Qi, Hui; Zhang, Weishi; Yang, Li; Lin, Zhenzhi
Abstract: The carbon emission right is considered as an effective way to reduce carbon emissions in the power industry, especially under the global goal of carbon neutral. Considering that carbon emission cost will affect long-term profits, the bidding strategies of power generation companies in electricity market and carbon emission market need to be coordinated. Given this background, a bi-level bidding strategies optimization model is proposed for power generation companies, which considers the carbon emission right and aims to maximize their annual power generation benefits. The purchase of carbon emission right at the beginning of the year is optimized in the upper-level model with the goal of maximizing the expected annual income and the uncertainty of transaction volume in monthly bidding market considered. The remaining carbon quota, penalty electricity price, and uncertainty of the competitor's quotation in monthly electricity market are considered in the lower-level model, based on which the bidding strategy for power generation company with the goal of maximizing the monthly expected income is proposed, and the power generation company's electricity market bidding model and its clearing results are simulated. Simulation results shows that power generation companies' purchases of carbon emission rights and their bidding strategies in the monthly market are affected by the carbon emission penalty price. The higher the penalty price is, the greater the quotation and the purchase of carbon emission rights are.